Panem et circenses / Bread and circuses – nowadays - Węglarz, Józef (Health Promotion & Physical Activity, 2017)
Human needs have their own hierarchy and are significantly dependent on the lifestyle of the individual. They are also culturally conditioned. The satisfaction of one’s needs determines the level of human existence and location of a person in social structures as well as individual preferences. Taking care of the body, in our world, can be understood in two ways. On the one hand it is a socially postulated custom encouraging to participate in a physical culture and on the other hand it is an act of individual choice. The latter marks the attitude towards physical affection as a need. Body kindness must be taught by showing its value. This is to be done, among others, by physical education as an organised pedagogical process.